Anteroposterior Diameter of the Left Atrium Determines the Occurrence of Left Atrial Tachycardia in Non-paroxysmal Atrial Fibrillation Patients after Catheter Ablation - Hanafy, Dicky Armein; Chang, Hung-Yu; Lin, Yenn-Jiang; Chang, Shih-Lin; Hu, Yu-Feng; Chen, Shih-Ann (Jurnal Kardiologi Indonesia, 2023)
Objectives: The relationship between left atrial (LA) size and atrial fibrillation (AF) is well-established. However, the specifics of LA regional remodeling and its connection to left atrial tachycardia (LA-AT) post-ablation in patients with non-paroxysmal AF are less understood. This study aims to explore how LA dimensions are related to the development of LA-AT following AF ablation procedures in these patients. Methods: This study focused on 73 patients with non-paroxysmal atrial fibrillation (average age 52, predominantly male, with a nearly even split between persistent and long-lasting persistent AF), all undergoing their first catheter ablation for AF. Prior to the ablation, left atrial dimensions were determined through computed tomography, measuring the maximal transverse, anteroposterior, and superoinferior diameters. Results: Over an average follow-up period of 23 months, 31.5% of the patients (Group 1) experienced left atrial tachycardia (LA-AT) that required a second linear ablation procedure. This group had significantly larger left atrial (LA) dimensions in terms of transverse, anteroposterior, and superoinferior measurements compared to the other group (Group 2). However, the recurrence of atrial fibrillation (AF) was not linked to any specific LA diameter. The anteroposterior diameter was identified as a significant predictor (p=0.002, HR 2.3, 95% CI 1.3-3.8) for LA-AT occurrence through multivariate analysis. Conclusions: Eccentric dilatation involving the anteroposterior diameter is a significant predictor for the occurrence of LA-AT in patients with non-paroxysmal AF after catheter ablation. Keywords Atrial fibrillation; Atrial flutter; Atrial tachycardia; Left atrial diameter; Catheter ablation; Computed tomography